2009
DOI: 10.1111/j.1532-5415.2009.02177.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Sleep Duration and Hypertension in Older Spanish Adults

Abstract: Self-reported sleep duration is not associated with hypertension in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 22 publications
(48 reference statements)
6
37
1
Order By: Relevance
“…17 Therefore, while many epidemiological studies have suggested a relationship between sleep duration and HT in middleaged insomnia patients, the results are confl icting in the elderly population, with some studies stressing the independent risk of short sleep for HT 13,[18][19][20][21] and other studies fi nding no association. [22][23][24][25][26] The discrepancies among these reports likely stem…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 54%
“…17 Therefore, while many epidemiological studies have suggested a relationship between sleep duration and HT in middleaged insomnia patients, the results are confl icting in the elderly population, with some studies stressing the independent risk of short sleep for HT 13,[18][19][20][21] and other studies fi nding no association. [22][23][24][25][26] The discrepancies among these reports likely stem…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 54%
“…[14][15][16][17][18] Recently, growing evidence has suggested that short or long sleep duration might be associated with hypertension risk. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] However, the results have been inconsistent, which could be due to the differences in the studied population, the study design and insufficient statistical power.…”
Section: Introductionmentioning
confidence: 85%
“…21 However, one study reported the OR value of short sleep duration for incident hypertension without the specific definition of sleep duration. 22 Hypertension was defined as systolic blood pressure/diastolic blood pressure (SBP/DBP)X140/90 mm Hg, current use of antihypertensive drugs or self-report of physician's diagnosis in all of the studies except for the one by van den Berg et al 24 (which defined hypertension as SBP/DBPX160/100 mm Hg or current use of antihypertensive drugs) and the study by Wang et al 31 (using SBP/DBPX130/85 mm Hg or physician diagnosed hypertension as the definition).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep deprivation among women (≤5 hours versus 7 hours/night) is associated with a greater risk of hypertension (odds ratio: 1.68, 95% confidence interval, 1.39–2.03) than that observed among men (odds ratio: 1.30; 95% confidence interval, 0.93–1.83); however, only 3 out of 23 reviewed studies presented findings stratified by sex 16, 17, 18, 19. Prolonged sleep onset latency increases the odds of hypertension by 300% (odds ratio: 3.27; 95% confidence interval, 1.20–8.96) 20.…”
Section: Introductionmentioning
confidence: 96%